Characterization and Optimization of a Collinear Array of Circularly Polarized Side-Mounted Elements - Gerino P. Mappatao; Pinky Tumaliuan-Jimenez (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper presents the radiation characteristics of a two-element collinear array of shunt-fed, slanted dipoles side-mounted to a metallic tower. It presents the radiation characteristics of the array as commonly implemented by FM broadcasters and suggests methods on how to optimize these characteristics such as the power gain, pattern circularity, side-lobe reduction, and horizontal-vertical polarization component ratio for the array to better conform to broadcast standards. By determining these characteristics using an advance antenna simulation software, optimization variables are identified, and their optimized values are determined. The optimized values lead to improved radiation characteristics of the array in conforming with broadcast requirements. Results show that adjusting the distance between the dipoles to less than one wavelength reduces the sidelobe of the array radiation pattern; varying the dipole physical specifications improves the polarization component ratio and the circularity of the radiation pattern. However, varying the dipole specifications also reduces the gain of the array. For applications requiring higher gains, other methods of realizing high collinear array gains are recommended.